Activation of cancer immunotherapy by nanomedicine - Lijuan Wang; Henan Xu; Lili Weng; Jin Sun; Ye Jin; Chunping Xiao (Frontiers Media S.A., 2022)
Cancer is one of the most difficult diseases to be treated in the world. Immunotherapy has made great strides in cancer treatment in recent years, and several tumor immunotherapy drugs have been approved by the U.S. Food and Drug Administration. Currently, immunotherapy faces many challenges, such as lacking specificity, cytotoxicity, drug resistance, etc. Nanoparticles have the characteristics of small particle size and stable surface function, playing a miraculous effect in anti-tumor treatment. Nanocarriers such as polymeric micelles, liposomes, nanoemulsions, dendrimers, and inorganic nanoparticles have been widely used to overcome deficits in cancer treatments including toxicity, insufficient specificity, and low bioavailability. Although nanomedicine research is extensive, only a few nanomedicines are approved to be used. Either Bottlenecks or solutions of nanomedicine in immunotherapy need to be further explored to cope with challenges. In this review, a brief overview of several types of cancer immunotherapy approaches and their advantages and disadvantages will be provided. Then, the types of nanomedicines, drug delivery strategies, and the progress of applications are introduced. Finally, the application and prospect of nanomedicines in immunotherapy and Chimeric antigen receptor T-cell therapy (CAR-T) are highlighted and summarized to address the problems of immunotherapy the overall goal of this article is to provide insights into the potential use of nanomedicines and to improve the efficacy and safety of immunotherapy.